Dynamics of the binary black hole system in quasar OJ287 - A. V. Bogdan; B. I. Hnatyk (Вісник Астрономічної школи, 2011)
In our paper a simulation of light curve of quasar OJ287 is curried out. We consider the evolution of a binary black hole system, in which the passage of a less massive component through the accretion disk of a more massive component creates a flash of radiation in the optical range. The comparison of calculated and observed moments of outbursts allows to estimate the parameters of the system, calculate its further evolution, and in particular to predict the characteristics of gravitational radiation.